011 Ex-vivo generation of plasmin from patients with acute ischaemic stroke is predictive of successful thrombolysis. Issue 6 (24th May 2018) - Levi, Chris; Lillicrap, Thomas; Harman, Stevi; Draxler, Dominik; Niego, Be'Eri; Ho, Heidi; McCutcheon, Fiona; Kleinig, Timothy; Koblar, Simon; Hamilton-Bruce, Monica Anne; Garcia-Esperon, Carlos; Lincz, Lisa; et al.
Abstract : Introduction: Thrombolysis with recombinant tissue-type plasminogen activator (rt-PA) fails in more than 60% of patients with acute ischaemic stroke (AIS). Simultaneously, there are risks associated with the use of rt-PA, including the risk of symptomatic intracranial haemorrhage (sICH) even in patients who do re-canalise. While thrombus location, aetiology and infarct size can affect the likelihood of successful thrombolysis, other factors distinguishing patients who re-canalise from those who don't have yet to be fully elucidated. The ability of rt-PA to promote thrombolysis is dependent upon its capacity to generate plasmin, and we set out to test this capacity ex-vivo . We hypothesised that patients with low plasmin generating capacity are less likely to re-canalise following rt-PA treatment. Methods: Plasma was obtained from 90 AIS patients up to 1 hour before thrombolysis and screened for baseline levels of plasminogen, anti-plasmin, and plasmin-anti-plasmin (PAP) complexes. The degree of inducible plasmin generation was determined using amidolytic assays following ex-vivo addition of rt-PA for 1 hour. ELISA assays were also used to quantitate the fold-increase in PAP complex levels after rt-PA treatment. Results: rt-PA inducible PAP levels, a surrogate for the capacity to generate plasmin from plasminogen, varied dramatically between patients. The ratio of post-thrombolysis PAP to pre-thrombolysis PAP ranged from 3.4 to 105.9 within the cohort examined for this study. Multivariate regression analyses revealed that each fold increase in PAP levels was associated with a 4.2% increase in the odds of recanalisation (p=0, 035) when corrected for blood glucose levels. Conclusion: This is the first report of ex vivo -inducible plasmin generation as a predictor of thrombolysis. The predictive power of this screening assay for sICH is still under investigation.